Solar energy engineering of solor energy systems - Kolisnychenko, Stanislav (Trans Tech Publications, Ltd., 2015)
The collection "Engineering of Solar Energy Systems" consists of papers published by Trans Tech Publications Inc. from 2010 to 2014 inclusive and covers a wide range of advanced achievements in the field of creating and designing systems for technological use of solar energy